Entrepreneurship and Economic Growth: Literature Review - Hamdana, Allam; Almubarak, Muneer; M. Sarea, Adel (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this paper is to review literature about the impact of entrepreneurship on economic growth. Previous studies tackled two trends on the relation between entrepreneurship and economic growth. The first trend stresses that entrepreneurship has an ascending impact on economic growth through increasing job opportunities and production. As for the second trend, it denies such an impact. Each of these trends has its justifications.